LANGUAGE STYLE OF HABIBURRAHMAN EL-SHIRAZY IN THE DWILOGY OF AYAT-AYAT CINTA: A STYLISTIC STUDY - Aflahah Aflahah (OKARA: Jurnal Bahasa dan Sastra, 2017)
Novel is an artwork which closely relates to human life and is considered as the representation of human life journey. The language style in novel is the embodiment of language use by an author to express ideas, emotion, opinion, and to give a certain effect. The main problem will be discussed in this study is the language style found in the novels of AAC 1 and 2. This study is about individual language style, an author’s language style who have written best seller novels, namely Habiburrahman El-Shirazy (HES). The approach that is considered very appropriate in understanding the language use of HES in Dwilogy of Ayat-Ayat Cinta (DAAC) is stylistic study. A stylistic study reveals how is the language style used by HES and what effects that are resulted. The approach of this research is a descriptive qualitative research. Descriptive method is used to describe the linguistic facts such as the language style based on lexical choice, sentence structure, and direct or indirect meaning. The use of language style based on lexical choice (diction) in DAAC shows a typical language style of HES as well as shows his ability as a Da’i and man of letters. The analysis of language style based on sentence structure and direct/indirect meaning illustrates the descriptive style of HES. Whatever he describes, it must be very accurate. He gives very detail information of the object being spoken of either background of the story or characterization. Through language style, HES describes the emotions experienced by the characters properly so it makes the readers able to empathize. From the data had been obtained, it reveals that language style used by HES to describe characters or characterization (describe the physical condition, characters, and characteristics), describes its background, tells the plot, and convey the message. The results showed the lexical choice of scientific words and religious words are typical of HES’s language style in his DAAC, the peculiarities of language style based on sentence structure in DAAC seen from the use of repetition (anaphora), and HES’s peculiarity in using language style according to direct or indirect meaning can be seen from the use of personification.